SME’s sustainability and the utilization of vegetable oil waste to support environmentally friendly production process - Ernie Hendrawaty; Agrianti Komalasari; Liza Alvia; Heru Wahyudi; R. Ribhan; Mohammad Bin Abdullah; Mohd. Lokman (Universitas Muhammadiyah Malang, 2023)
Community service is a process of self-empowerment for the benefit of society. The community empowerment movement, whatever its form, is part of community service. The problem regarding the large amount of vegetable oil waste for MSME actors both in Indonesia, especially in big cities is getting more complicated. The increasing amount requires immediate handling because it can damage the environment when disposed of carelessly. In this community service activity, the service team involved Micro, Small and Medium Enterprises in Bandar Lampung. In addition, this dedication also involves foreign university partners, namely the MARA University of Technology (UiTM) in its implementation. This service focuses on the utilization of vegetable oil waste that has been used and then used to produce value-added products such as biodiesel. This award will be held from 8 to 14 October 2022. The purpose of holding this service is how to manage used oil waste resulting from the MSME production process. This is because the waste oil produced is often just carelessly disposed of into the surrounding environment which will certainly have a negative impact on environmental sustainability. Later, when it becomes biodiesel, besides being an added economic value, it will also support environmental sustainability by creating an alternative source of renewable energy. The conclusion from this service is that the participants have the knowledge and ability to process waste vegetable oil into biodiesel.